New insights into the biological properties of Eucalyptus-derived essential oil: a promising green anti-cancer drug - Abiri, Rambod; Atabaki, Narges; Sanusi, Ruzana; Malik, Sonia; Abiri, Ramin; Safa, Parastoo; Ab Shukor, Nor Aini; Abdul-Hamid, Hazandy (Taylor and Francis Group, 2021)
Cancer is a condition in which cells grow uncontrollably and may metastasis to other parts of the body. Despite the recent advances in synthesising new anticancer agents, plant-derived compounds are traditionally considered as the primary health care approaches in some parts of the world. Eucalyptus-derived essential oils are the rich resources of active phytochemicals, which have been used for treating or preventing different ailments. However, there is less literature addressing the bioactivity of Eucalyptus-derived phytochemicals in the treatment of cancers. In this review paper, we summarised the existing evidence on the wide-spectrum activity of Eucalyptus-derived essential oil against malignancies. Our review highlighted that Eucalyptus-derived essential oil contains a wide variety of secondary metabolites, and thus capable of slowing or inhibiting the cancerous cell lines in vitro and in vivo conditions. We also summarized the achievement in the anti-tumour activity of nanoparticles, the application of plant-based essential oils in food safety, and the application of green extraction technologies. It can be concluded that Eucalyptus has immense potential to cure malignancies, and such information can be used in further studies. Notwithstanding the advantages, Eucalyptus-derived essential oils can be poisonous; therefore, more evidence is still required to confirm the efficacy of Eucalyptus-derived essential oil.